Innovative approaches targeting innate immune cells to promote organ transplant tolerance - Toyama, Chiyoshi; Thomson, Angus W. (Frontiers in Transplantation, 2026)
Achieving long-term allograft survival while minimizing systemic immunosuppression (IS) remains a critical unmet need in transplantation. While adaptive immunity has traditionally been the primary focus of IS therapy, innate immune cells—that include neutrophils, monocytes, macrophages, dendritic cells, myeloid-derived suppressor cells, innate lymphoid cells (ILCs), natural killer (NK) cells, and gamma delta (γδ) T cells act as key upstream orchestrators of allograft rejection and tolerance. Recent advances in single-cell RNA sequencing and spatial transcriptomics have unveiled the profound heterogeneity of these cell populations, identifying distinct regulatory subsets and novel inhibitory checkpoints. These high-resolution insights provide the scientific rationale for developing innovative precision therapies that can selectively modulate innate immune reactivity without compromising global immunity. Here, we review innovative strategies to target/amplify these mechanisms, including targeting the myeloid inhibitory checkpoints (e.g., leukocyte immunoglobulin-like receptor B; sialic acid-binding immunoglobulin-like lectin-E) to induce tolerogenic phenotypes. We further discuss the modulation of metabolic reprogramming to prevent “trained immunity” using mammalian target of rapamycin inhibitor (mTORi)-loaded nanoparticles, and the use of CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 gene editing to silence T cell costimulatory signals. We evaluate the adoptive transfer of regulatory myeloid cells, -specifically donor-derived regulatory macrophages and regulatory dendritic cells, and innate lymphoid cells in transplant recipients. Furthermore, the potential of targeting specific NK cell and ILC subsets associated with graft regulation is addressed. Collectively, these emerging approaches aim to reprogram the allograft microenvironment, offering a promising paradigm shift towards establishing transplant tolerance.